Vermitteln - Verbinden - Verstehen 46. Jahrestagung des Fachverbandes Deutsch als Fremd- und Zweitsprache an der Technischen Universität Chemnitz 2019 - Hinzmann, Friederike (Universitätsverlag Göttingen, 2021)
In recent years, the areas of German as a Foreign Language (GFL) and German as a Second Language (GSL) have taken quite different developmental paths. To unify these contrasts was the purpose of the 46th Annual Convention of the Association for German as a Foreign and a Second Language (FaDaF e.V.) in Chemnitz from 28 to 30 March 2019. The proceedings of this conference comprise contributions from both academic research and practice in the area of teaching German as a Foreign or Second Language as well as the Associations' resolution concerning the recent German Immigration Act for Skilled Workers. Thematically, the contributions focus on didactics and methodology of German language teaching, transnational networking and the many facets of understanding - from language comprehension to (intercultural) hermeneutics. Opening with contributions from the young academics' conference held prior to the annual convention, the volume Teaching - Networking - Understanding attempts to unify the many interfaces of research and practice.